Neurological typology and its role in enhancing technical and tactical skills in adolescent female boxers - Tyshchenko, м; Omelyanchik, H.; Markova, S.; Vorontsov, A.; Pavelko, O.; Doroshenko, E. Yu.; Sokolova, L.; Hlukhov, I.; Drobot, K.; Тищенко, В.; Омельяненко, Г.; Маркова, С.; et al. (My University, 2023)
Background. This article delves into the intricate typological characteristics of the nervous system and temperament, exploring their profound impact on accelerating the training and enhancement of technical and tactical skills in adolescent female boxers aged 12-15 years. Situated at the crucial stage of basic training, this study illuminates how individual neurotypological traits can significantly influence the efficacy and pace of skill acquisition in young athletes. Purpose. To identify individual typological features of girls aged 12-15 years in the process of boxing education at the stage of basic preparation. Material and Methods. The study was attended by skilled athletes (participants, prizes, championships of regional and international tournaments, Ukrainian championships in their age groups). Boxers, which are trained using basic preparation of Children's and Youth Sports School № 1 of Melitopol. To solve the tasks, the following methods of research have been used: theoretical analysis of special and scientific literature, materials of the Internet, summarizing data, mathematical statistics. Передумови. У статті розглядаються складні типологічні особливості нервової системи та темпераменту, досліджується їх глибокий вплив на прискорення тренування та вдосконалення технічних і тактичних навичок у дівчат-боксерок 12-15 років. Дослідження проведене на вирішальному етапі базової підготовки, показало, як окремі нейротипологічні особливості можуть суттєво впливати на ефективність та швидкість набуття навичок у юних спортсменок. Мета. Виявити індивідуально-типологічні особливості дівчаток 12-15 років у процесі навчання боксу на етапі базової підготовки. Матеріал та методи. У дослідженні взяли участь кваліфіковані спортсмени (учасниці, призерки першостей регіональних і міжнародних турнірів, чемпіонатів України у своїх вікових групах). Боксерки, що тренувалися на базі базової підготовки ДЮСШ №1 м. Мелітополя (Україна). Для вирішення поставлених завдань було використано такі методи дослідження: теоретичний аналіз спеціальної та наукової літератури, матеріалів мережі Інтернет, узагальнення даних, математична статистика.
Неврологічна типологія та її роль у вдосконаленні техніко-тактичних навичок у підлітків-боксерок
Doroshenko E. Yu. - https://orcid.org/0000-0001-7624-531X
Keywords: female boxing; girls aged 12-15 years; temperament; dominant type; tests; basic preparation; жіночий бокс; дівчатка 12-15 років; темперамент; домінуючий тип; випробування; базова підготовка